2012
DOI: 10.3233/s12349-012-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic and hypoglycemic properties of fibre-enriched cake in alloxan-induced diabetic rats

Abstract: Studies have provided evidence of the hypoglycemic properties of fiber-containing foods compared to fiber-free foods. In this study, the hypoglycemic properties and beneficial effects of fiber-enriched cake in alloxaninduced diabetic rats were reported. Diabetes was induced by a single intraperitoneal injection of alloxan. Fiberenriched cake was produced from selected fruits and fed to the treatment group. The rats were monitored daily for food intake, and body weight. Their blood glucose levels were monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…(2010) , the reduced creatinine level in treated diabetic rats indicates a higher level of hemoglobin and thus collating with the anti-anemic effect of the biscuit. Similar results were obtained by Erukainure et al. (2013b) where they found that fibre-enrich cake had a therapeutic effect against biochemical changes associated with diabetes mellitus.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…(2010) , the reduced creatinine level in treated diabetic rats indicates a higher level of hemoglobin and thus collating with the anti-anemic effect of the biscuit. Similar results were obtained by Erukainure et al. (2013b) where they found that fibre-enrich cake had a therapeutic effect against biochemical changes associated with diabetes mellitus.…”
Section: Resultssupporting
confidence: 83%
“…The optimum combination of Musa sapientum (‘ banane cochon ’) and Vigna unguiculata flour was determined using an augmented simplex lattice mixture design. This design generated different formulations of flour samples and the optimum composition was based on the reference lipid content of 18.75%, the protein content of 10.30% and a reducing sugar lower than 20.14% ( Erukainure et al., 2013a , 2013b ). Thus the proportion was as thus Musa sapientum (‘ banane cochon ’) 67.5g and Vigna unguiculata (cowpea) 17.5g, for a total mass of 85g of flour.…”
Section: Methodsmentioning
confidence: 99%
“…The increased SOD and CAT activities in the brain tissues of untreated diabetic rats further suggests incidence of oxidative stress. These observed increments can be attributed to increased synthesis owing to induction of oxidative stress [28] , [1] , [10] , [8] . Their reduced activities on feeding with the formulated cake further reflect the antioxidant protective potential of the snack against diabetes-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Banana ( Musa species ), oranges ( Citrus sinensis ), watermelon ( Citrullus lanatus ), pineapple ( Ananas cosmosus ) and pawpaw ( Carica papaya ) were purchased from Ketu fruit market, Ketu, Lagos, Nigeria. They were processed into fibre paste as described by Erukainure et al [10] , [9] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation